A Defense Industry Economy: The Concept of Dual-Use Technologies (Spin On & Spin Off) as an Effort to Accelerate the Independence of the Indonesian Defense Industry - Endro Tri Susdarwono (Program Studi Pendidikan Ekonomi, IKIP Budi Utomo Malang, 2021)
The purpose of this study discusses the concept of dual-use technologies (spin on and spin off) in an effort to accelerate the economic independence of the Indonesian defense industry. This research is a qualitative research, the type of research uses a comprehensive analytical study and analytical normative approach. The development of defense technology in addition to aiming at production independence that can compete with other countries' products, must also provide a multiplier effect. The strategy is clear: optimize the added value of the defense industry. To that end, the first step that must be taken is to encourage import substitution for the defense industry and, after the industry develops, the final step is to commercialize or spin off the spillover effect or defense industry multiplier effect in the form of products that can be used for civil benefit. Defense provides a direct advantage of technology and its influence on other sectors, where the spin-off is used by the civil sector which can increase growth. In developing countries, defense spending can increase growth if some portion of expenditure is used for the provision of social infrastructure. Defense spending provides protection for citizens, where internal and external security will increase exchange in the market.